(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper argues that changing attitudes to the landscape as depicted in the Malayalam film Ividam Swargamanu (It is Heaven Here) (2009) depend on individual perception, which is influenced by social, political, and economic factors